Legal Protection of Bank Customer Regarding Bank Credit Agreements According to the Consumer Protection Law - Sinambela, Hotman (PT. Riset Press International, 2023)
The main objective of the research is to find out, describe and analyze whether the standard clauses in Rural Bank credit agreements (BPR) reflect the credit agreement and do not conflict with the principles of freedom of contract and the principle of balance as well as the impact of implementing standard clauses in Rural Bank credit agreements and legal protection. against customers who are harmed by the application of the standard clause. The research results reveal that the application of standard clauses in BPR credit agreements has fulfilled the principles of freedom of contract, balance and the principle of consensualism because in their application they still open up room for negotiation with customers so that an agreement is reached. The impact of implementing the standard clauses of Rural Bank credit agreements on customers' rights as consumers is that customers do not have room to defend their rights or to file complaints due to the application of standard clauses which are detrimental or burdensome, especially with the